A Sn self-doped Pb-MOF photocatalyst and its preparation method and application

By reducing lead-containing hazardous waste and reacting with tripolymer thiocyanic acid, Sn self-doped Pb-MOF photocatalyst is prepared, which solves the high cost and high energy consumption problems of photocatalytic preparation of H2O2 in the prior art, and achieves a high activity and stable photocatalytic effect.

CN117772283BActive Publication Date: 2025-04-01SUN YAT SEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311592813.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-04-01
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

The prior art has problems of high cost, high energy consumption, high temperature and high pressure preparation in the photocatalytic preparation of hydrogen peroxide (H2O2), and lacks high activity and stable photocatalysts.

Method used

By reducing lead-containing hazardous waste through liquid phase and reacting with tripolymer thiocyanic acid, and polymerizing by low-temperature solvent thermal method, Sn self-doped Pb-MOF photocatalyst was prepared.

Benefits of technology

Low-cost and low-energy consumption photocatalyst preparation is achieved, with high activity and stability, and it shows excellent efficiency and long-term stability in the photocatalytic preparation of H2O2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117772283B_ABST
    Figure CN117772283B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal organic framework material preparation and photocatalysis, and discloses a Sn self-doped Pb-MOF photocatalyst and its preparation method and application. The preparation method is as follows: the lead-containing hazardous waste is reduced by an acid solution containing a reducing agent to obtain a soluble lead solution, and an organic ligand trithiocyanate is added to carry out a low-temperature polymerization reaction. After cooling, centrifugation, washing, and drying, a series of Sn self-doped Pb-MOF photocatalysts are obtained, and they are used for photocatalytic preparation of H2O2. The Pb(Sn)-MOF photocatalyst exhibits an excellent H2O2 production rate, which can reach up to 2023.76μmol . g ‑1. h ‑1 , which is 1.5 times that of pure Pb-MOF, and has good stability. The present invention prepares Sn self-doped Pb-MOF photocatalyst with photosensitivity effect from lead-containing hazardous waste, improves the efficiency of Pb-MOF in producing H2O2, and expands new ways to utilize lead-containing hazardous waste at a high value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal organic framework material preparation and photocatalysis, and specifically relates to a Sn self-doped Pb-MOF photocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen peroxide, also known as hydrogen peroxide, is a green and environmentally friendly oxidant that is widely used in many fields such as medicine, chemicals, and textiles. The global annual demand for H2O2 is about 4 million tons, and this number continues to increase. It is expected that by 2027, the market demand for H2O2 will increase to 5.7 million tons. At present, the main method for commercial production of H2O2 at home and abroad is the anthraquinone method. Although it has the advantages of low cost and large synthesis volume, it is contrary to the concept of modern green chemistry because it not only involves multi-step reactions of high-energy hydrogenation and oxidation, but also requires large-scale production plants to minimize capital investment and obtain high-concentration H2O2 to reduce transportation costs. Therefore, it is extremely challenging to develop safe, efficient, energy-saving and environmentally friendly production of H2O2.

[0003] Emerging photocatalytic technology uses H2O and O2 as raw materials and inexhaustible sunlight as an energy source, and is considered to be a highly promising green development solution. At present, one of the main challenges in the research on photocatalytic preparation of H2O2 is to find highly active and stable photocatalysts. In recent years, metal-organic frameworks (MOFs) have provided a new platform for the development of new photocatalysts due to their uniform pores, high specific surface area and porosity, structural controllability, and thermochemical stability. For example, MIL-53 (Fe) and ZIF-8 are used for the degradation of pollutants (CN201910479376.8); NH2-MIL-125 (Ti) is used for the reduction of Cr (VI) (CN201811392251.3); UIO-66 is used for hydrogen production (DOI: 10.1039 / c3ee40507a). However, there are few reports on related research on Pb-MOF, especially in the preparation of H2O2. In addition, it is worth noting that the vast majority of MOFs photocatalysts are currently prepared using chemical reagents as raw materials and are prepared at high temperature and high pressure using a reactor, which leads to problems such as high preparation cost and high energy consumption, limiting their further application.

[0004] In view of the shortcomings and disadvantages of the above-mentioned existing technologies, practical and effective methods must be adopted. Under the background of "dual carbon" and sustainable development, it is of great significance to realize the multi-metal active sites, low-cost, green and controllable preparation of photocatalysts with the help of large amounts of lead-containing solid hazardous waste. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a Sn self-doped Pb-MOF photocatalyst, which uses lead-containing hazardous waste as a lead source, is reduced in the liquid phase, and then an organic ligand, trithiocyanate, is added and polymerized by a low-temperature solvent thermal method.

[0006] Another object of the present invention is to provide a Sn self-doped Pb-MOF photocatalyst prepared by the above method.

[0007] Another object of the present invention is to provide application of the above Sn self-doped Pb-MOF photocatalyst.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a Sn self-doped Pb-MOF photocatalyst comprises the following steps:

[0010] The lead-containing hazardous waste is reduced with an acid solution containing a reducing agent to obtain a soluble lead solution, and an organic ligand, thiocyanate, is added to carry out a low-temperature polymerization reaction. After the reaction, the product is cooled, centrifuged, washed, and dried to obtain a Sn self-doped Pb-MOF photocatalyst, referred to as Pb(Sn)-MOF.

[0011] Preferably, the reducing agent is one of hydrogen peroxide and hydrazine hydrate;

[0012] The acid solution is one of acetic acid and nitric acid.

[0013] Preferably, the low-temperature polymerization reaction conditions are: heating the reaction in an oil bath at 80° C.-140° C. for 12 h-36 h.

[0014] Preferably, the lead-containing hazardous waste is one of a waste lead paste desulfurization smelting precursor, waste lead-tin alloy, solder, and tin paste waste slag, and more preferably a waste lead paste desulfurization smelting precursor, obtained by referring to the method in CN113215413A.

[0015] Preferably, the molar ratio of lead to thiocyanate in the lead-containing hazardous waste is 1 to 10:1, more preferably 1 to 1.6:1.

[0016] Preferably, the thiocyanuric acid is dissolved in dimethyl sulfoxide and reacted with a soluble lead solution.

[0017] Preferably, the acid solution containing the reducing agent is added by injection, titration or peristaltic pump addition.

[0018] Preferably, the molar ratio of lead in the lead-containing hazardous waste, the reducing agent and the acid solution is 1:1-10:2-20, more preferably 1:1-1.3:2-2.3, and more preferably 1:1.1:2.1.

[0019] Preferably, the reaction equation for reducing the lead-containing hazardous waste with an acid solution containing a reducing agent to obtain a soluble lead solution is as follows:

[0020] PbO2+H2O2+2CH3COOH=Pb(CH3COO)2+2H2O+O2↑

[0021] Preferably, the lead molarity in the soluble lead solution is ≤0.04 mol / L, and the volume is ≤50 mL.

[0022] Preferably, the centrifugation condition is 4000-6000 rpm for 10-30 min;

[0023] Preferably, the washing is performed by washing with acetone and deionized water three times respectively;

[0024] The drying conditions are freeze drying, the temperature is -50°C-50°C, and the drying time is 12h-24h.

[0025] A Sn self-doped Pb-MOF photocatalyst is prepared by the above method.

[0026] Application of the above Sn self-doped Pb-MOF photocatalyst in the preparation of H2O2.

[0027] Preferably, the application comprises the following steps:

[0028] The Pb(Sn)-MOF photocatalyst and formic acid solution were evenly mixed, and the reaction gas was continuously introduced under light-proof conditions. After reaching adsorption equilibrium, H2O2 was prepared by photocatalysis under visible light.

[0029] Preferably, the dosage of the photocatalyst in the reaction system is 0.05 g / L to 0.1 g / L, the reaction gas is O2, the flow rate is 10 mL / min to 50 mL / min, the illumination time is 10 min to 60 min, and it is carried out under the illumination condition of a 300W xenon lamp.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] (1) The preparation method of the catalyst of the present invention is simple and the preparation conditions are easy to control. Some of the necessary reagents used are derived from hazardous wastes, which reduces the preparation cost of the materials on the one hand and the environmental risk of lead-containing hazardous wastes on the other hand, providing a new direction for the sustainable high-value utilization of solid / hazardous wastes and the low-cost preparation of materials.

[0032] (2) The Sn in the photocatalyst of the present invention is derived from lead-containing hazardous wastes such as desulfurization smelting precursors of waste lead paste, waste lead-tin alloys, solder, and tin paste waste residues. The self-doping of Sn has the advantages of increasing the adsorption capacity of O2, enhancing the light absorption capacity, and improving the photogenerated e - -h+ It has multiple functions such as separation efficiency and improved internal electric field.

[0033] (3) The Pb(Sn)-MOF photocatalyst prepared by the present invention does not contain precious metals and can exhibit excellent photocatalytic efficiency up to 2023.76 μmol.g in the process of photocatalytic preparation of H2O2 without adding any co-catalyst. -1 .h -1 .

[0034] (4) The Pb(Sn)-MOF photocatalyst prepared by the present invention has good stability and maintains a good linear relationship (R 2 =0.992). BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of the preparation of the material.

[0036] Figure 2 X-ray diffraction patterns of the Pb(Sn)-MOF series prepared in Examples 1 to 4 of the present invention and the Pb-MOF photocatalyst of Comparative Example 1.

[0037] Figure 3 Infrared spectra of the series of Pb(Sn)-MOF photocatalysts prepared in Examples 1 to 4 of the present invention and the Pb-MOF photocatalyst of Comparative Example 1.

[0038] Figure 4 These are SEM images of the Pb-MOF prepared in Comparative Example 1 of the present invention and the Pb(Sn)-MOF-3 photocatalyst prepared in Example 3.

[0039] Figure 5 TEM image element distribution diagram of the Pb(Sn)-MOF-3 photocatalyst prepared in Example 3 of the present invention.

[0040] Figure 6 are the element characteristics of Pb and Sn in the periodic table in Example 2 of the present invention.

[0041] Figure 7 This is the synchrotron radiation characterization of Pb(Sn)-MOF-3 and Pb(Sn)-MOF-4 in Examples 3 to 4 of the present invention.

[0042] Figure 8 This is an energy diagram of the Sn-doped MOF with 7-coordinated or 8-coordinated Pb sites and optimized structure in an embodiment of the present invention.

[0043] Fig. 9 This is the standard curve of H2O2 in Example 5 of the present invention.

[0044] Fig.10This is a comparison chart of the reaction rates of photocatalytic H2O2 production in Example 5.

[0045] Fig.11 This is a stability experiment of Pb(Sn)-MOF-3 photocatalyst. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0047] The preparation flow chart of the Pb(Sn)-MOF material prepared in the following examples is as follows Figure 1 shown.

[0048] The desulfurization smelting precursor of waste lead paste used in the embodiment is obtained by the method of patent CN113215413A, specifically the nitric acid leaching residue obtained in Example 7, wherein the purity of lead dioxide is 93.7%.

[0049] Example 1

[0050] 0.255g of waste lead paste desulfurization smelting precursor (theoretical lead dioxide molar amount is 1.0mmol) was added to 30mL deionized water containing 112.5 microliters of 30% hydrogen peroxide (4.1625g / L) and 119.7 microliters of acetic acid (4.1895g / L), stirred at room temperature until a clear solution was obtained, the lead acetate liquid was collected and the inner surface of the reactor was washed with deionized water to avoid the residue of the substance, and the above solution was added to deionized water and the volume was fixed to 50.0mL. Trithiocyanic acid (H3TTC, 177.2mg, 1.0mmol) was dissolved in dimethyl sulfoxide (50mL). The two solutions were then mixed in a 200 mL round bottle and heated at 100 °C for 24 h in an oil bath for low-temperature polymerization. The solution was cooled to room temperature and centrifuged (4000 rpm, 5 minutes) for solid-liquid separation. The solid was then washed three times with acetone and deionized water respectively, and then placed in a freeze dryer for 12 hours. The yellow material prepared above was recorded as Pb(Sn)-MOF-1.

[0051] Example 2

[0052] Different from Example 1, under the condition of fixed thiocyanate (177.2 mg, 1.0 mmol), the molar amount of lead in the waste lead paste desulfurization smelting precursor was adjusted to 1.2 times of thiocyanate, and the prepared yellow material was recorded as Pb(Sn)-MOF-2.

[0053] Example 3

[0054] Different from Example 1, under the condition of fixed thiocyanate (177.2 mg, 1.0 mmol), the molar amount of lead in the waste lead paste desulfurization smelting precursor was adjusted to 1.4 times of thiocyanate, and the prepared yellow material was recorded as Pb(Sn)-MOF-3.

[0055] Example 4

[0056] Different from Example 1, under the condition of fixed thiocyanuric acid (177.2 mg, 1.0 mmol), the molar amount of lead in the waste lead paste desulfurization smelting precursor was adjusted to 1.6 times of thiocyanuric acid, and the prepared yellow material was recorded as Pb(Sn)-MOF-4.

[0057] Comparative Example 1

[0058] The desulfurization smelting precursor of waste lead paste was replaced by high-purity lead dioxide chemical reagent (0.239 g), and the preparation process of Example 1 was repeated. The prepared yellow material was recorded as Pb-MOF.

[0059] X-ray diffraction analysis was performed on the materials prepared in Examples 1 to 4 and Comparative Example 1. Figure 2 The results show that the characteristic peaks of Pb-MOF match well with the simulation card of Pb-MOF, indicating the successful preparation of the material. Figure 2 , with the increase of the amount of precursor added to the desulfurization smelting of waste lead paste (the mass of fixed organic ligands), the characteristic peaks shifted to large angles as a whole, which indicates that some impurities entered the lattice structure of the lead-based metal-organic framework during the preparation of the material. In addition, the characteristic peaks of the lead-based metal-organic framework shifted to large angles, indicating that the ionic radius of the impurities was smaller than that of the lead ion.

[0060] The changes of the main chemical bonds in the series of Pb(Sn)-MOF and Pb-MOF photocatalysts were obtained by FT-IR. In the FT-IR spectrum of pure Pb-MOF, at 1213.8 cm -1 、845.6cm -1 、1404.3cm -1 The corresponding peaks are v(N2CS), δ(C3N3) (out-of-plane bending of the ring sextant) and -C=N- (in-plane triazine ring vibration). With the increase of the molar ratio of PbO2:H3TTC, the infrared characteristic peaks gradually shift to high wavenumbers ( Figure 3 ), it may be that the increase in the self-doping amount of impurities in the PbO2 precursor of the waste lead paste desulfurization smelting changes the coordination environment of the internal chemical bonds of Pb-MOF.

[0061] In order to clarify the effect of impurities on the morphology of Pb-MOF, Pb-MOF and Pb(Sn)-MOF-3 were tested by scanning electron microscopy. The results showed that Pb-MOF materials showed small particle morphology, while Pb(Sn)-MOF-3 series materials showed flower-like nanoclusters as a whole ( Figure 4 The change in morphology may be due to the chelation of impurity ions and ligand thiocyanate, which grows along different growth axes, resulting in the appearance of flower-like nanoclusters rather than particles.

[0062] The element distribution of Pb-MOF and Pb(Sn)-MOF-3 photocatalysts was analyzed by transmission electron microscopy. Compared with Pb-MOF, Pb(Sn)-MOF-3 contained Sn in addition to C, N, S in the ligand and lead in lead dioxide, indicating that Sn was involved in the synthesis of Pb-MOF photocatalyst ( Figure 5 ). From the periodic table, Sn and Pb are in the same main group, Sn is in the fifth period, and Pb is in the sixth period. The nuclear charge number of Pb is 82, which is much larger than the nuclear charge of Sn, which is 50. The outer layer of Pb atom has 4 electrons, but because the nuclear charge number is 82, it has a strong attraction to the outermost 4 electrons, so usually Pb can only lose 2 electrons. Therefore, the activity of Pb element is not as active as that of Sn element, resulting in Sn reacting with ligands first in the preparation process of materials ( Figure 6 ). Furthermore, the synchrotron radiation was used to analyze Pb(Sn)-MOF-3 and Pb(Sn)-MOF-4. The results showed that there was no obvious metal bond in the bulk phase of the photocatalyst, which preliminarily ruled out the possibility of Sn particles or clusters. In addition, the valence state of Pb(Sn)-MOF-4 is higher than that of Pb(Sn)-MOF-3 ( Figure 7 ).

[0063] The optimized structure of pure Pb-MOF was constructed using DFT, and based on this, Sn was used to dope the 7-coordinated or 8-coordinated Pb sites in MOF and optimize their structures. The results showed that the formation energy of 7-coordinated Pb sites (-48.5 kcal / mol) was smaller than that of 8-coordinated Pb sites (-37.6 kcal / mol), indicating that Sn preferentially doped the 7-coordinated Pb sites in Pb-MOF ( Figure 8 ). In summary, the presence of heteroatom Sn in the desulfurization smelting precursor of waste lead paste preferentially self-doped the 7-coordinated Pb sites of Pb-MOFs and entered the Pb-MOF lattice structure in the form of S-Pb-N chemical bonds.

[0064] Example 5

[0065] The materials prepared in Examples 1 to 4 and Comparative Example 1 were subjected to a photocatalytic H2O2 production experiment, and the specific steps were as follows:

[0066] First, 5.0 mg of lead-based metal organic framework photocatalysts, Pb(Sn)-MOF-1, Pb(Sn)-MOF-2, Pb(Sn)-MOF-3, Pb(Sn)-MOF-4 and Pb-MOF, were accurately weighed and added to a photocatalytic reactor with a magnetic rotor. Then, 95 mL of deionized water and 5 mL of formic acid were accurately pipetted with a 5 mL pipette and placed in an ultrasonic machine for ultrasonication until they were completely dispersed to form a uniform solution. Subsequently, the mixture was continuously stirred with oxygen at a rate of 20 mL / min in the dark for 30 minutes to allow the photocatalyst and the dissolved oxygen in the formic acid aqueous solution to reach an adsorption-desorption equilibrium. At the same time, a xenon lamp was turned on for preheating treatment. A 300 W xenon lamp was used as the light source and equipped with a 420 nm filter. Oxygen was continuously introduced during the entire reaction process, and the temperature of the photocatalytic reaction solution (-5°C to -10°C) was controlled by a low-temperature thermostat. After the light source is started (working current is 17A), at a fixed time interval of 30 minutes, use a pipette to accurately take 1mL of the reaction solution from the reactor, use a filter to filter out the excess catalyst, and absorb 0.3mL of the H2O2 concentration in the filtered reaction solution.

[0067] The determination was carried out by iodine titration, and the specific operation steps were as follows: 1.0 mL of C8H5KO4 (0.1 mol / L) and KI (0.4 mol / L) were added to 0.3 mL of the filtered reaction solution, respectively. After standing for 30 minutes under light-proof conditions, the characteristic absorption peak intensity was measured at 350 nm using a UV-visible spectrophotometer, and the standard curve method (such as Fig. 9 The concentration of H2O2 solution was determined as shown). Fig.10 This is a comparison chart of the reaction rates of the materials prepared in the example to prepare H2O2 under visible light radiation. It can be seen that the H2O2 generation rate of pure Pb-MOF is 1383.98 μmol.g -1 .h -1 The H2O2 generation rate of Pb(Sn)-MOF-3 reached 2023.76 μmol.g -1 .h -1 , which is 1.5 times that of pure Pb-MOF. Furthermore, the stability of Pb(Sn)-MOF-3 photocatalyst was tested under the time dimension (0min, 30min, 60min, 90min, 120min). The results showed that Pb(Sn)-MOF-3 still maintained a good linear relationship (R 2 =0.992)( Fig.11 ), which indicates that Pb(Sn)-MOF-3 has the ability to produce H2O2 continuously and with high stability.

[0068] Sn self-doping has a significant promoting effect on the performance of Pb-MOF photocatalytic preparation of hydrogen peroxide, mainly because it improves the adsorption capacity of O2, the light absorption capacity, and the separation of photogenerated electrons and holes.

[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing Sn self-doped Pb-MOF photocatalyst, characterized in that: The following steps are involved: The lead-containing hazardous waste is reduced by an acid solution containing a reducing agent to obtain a soluble lead solution, and an organic ligand trithiocyanate is added to carry out a low-temperature polymerization reaction. After the reaction is completed, the product is cooled, centrifuged, washed, and dried to obtain a Sn self-doped Pb-MOF photocatalyst; The lead-containing hazardous waste is a type of waste lead paste desulfurization smelting precursor, waste lead-tin alloy, solder, and tin paste waste slag.

2. The method for preparing a Sn self-doped Pb-MOF photocatalyst according to claim 1, characterized in that: The reducing agent is one of hydrogen peroxide and hydrazine hydrate; The acid solution is one of acetic acid and nitric acid.

3. The method for preparing a Sn self-doped Pb-MOF photocatalyst according to claim 1, characterized in that: The low-temperature polymerization reaction conditions are: heating the reaction in an oil bath at 80° C.-140° C. for 12 h-36 h.

4. The method for preparing a Sn self-doped Pb-MOF photocatalyst according to claim 1, characterized in that: The molar ratio of lead to thiocyanate in the lead-containing hazardous waste is 1 to 10:

1.

5. The method for preparing a Sn self-doped Pb-MOF photocatalyst according to claim 1, characterized in that: The acid solution containing the reducing agent is added by injection, titration or peristaltic pump addition.

6. The method for preparing a Sn self-doped Pb-MOF photocatalyst according to any one of claims 1 to 5, characterized in that: The molar ratio of lead, reducing agent and acid solution in lead-containing hazardous waste is 1:1~10:2~20.

7. A Sn self-doped Pb-MOF photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the Sn self-doped Pb-MOF photocatalyst according to claim 7 in the preparation of H2O2.

9. The use according to claim 8, characterized in that: The steps include: The Sn self-doped Pb-MOF photocatalyst and formic acid aqueous solution were evenly mixed, and the reaction gas was continuously introduced under light-proof conditions. After reaching adsorption equilibrium, H2O2 was prepared by photocatalysis under visible light.

Citation Information

Patent Citations

  • Preparation method and applications of nanometer titanium dioxide @ Fe-based MOF visible light composite catalyst

    CN109289927A

  • Preparation method for Ce-MOF material with methyl orange photocatalytic degradation function

    CN110270374A

  • Desulfurizing agent and method for preparing zero-carbon smelting precursor by removing sulfur in waste lead plaster

    CN113215413A

  • Fluorescent perovskite nanocrystal, and preparation method and application thereof

    CN109423278A

  • Method for preparing lead powder through wet recovery of waste lead plaster in leaching acid circulation

    CN113088684A